Erdheim-Chester disease: unveiling hidden manifestations through two case reports - Zhang, Guoxia; Yang, Xiaoqing; Fang, Lei; Cheng, Yuxia; Duan, Yanhua; Cui, Jing (Frontiers in Oncology, 2025)
We present two cases of Erdheim-Chester disease (ECD) in 66-year-old female patients, highlighting their distinct clinical manifestations and diagnostic challenges. The first patient presented with chest tightness and dyspnea, revealing pericardial effusion and hypermetabolic foci in multiple organs on imaging. Histopathological analysis indicated abundant foamy histiocytes, confirming ECD. Significant reduction in metabolic lesions following cladribine treatment. The second patient developed subcutaneous nodules post-hysterectomy, later diagnosed with mixed lobular panniculitis. Subsequent biopsies revealed similar histiocyte profiles, leading to ECD diagnosis. She responded well to an immunomodulatory regimen. Notably, whole-exome sequencing detected a MAP2K1 mutation in the second case, ​which lacked​ the BRAF V600E mutation commonly associated with ECD. These cases underscore the importance of thorough diagnostic evaluation and highlight the variability in clinical presentation and genetic alterations of ECD, contributing to improved recognition and management strategies for this rare condition.